Renal Transplantation after Transcatheter Aortic Valve Replacement: Case Report - Gangadharan, Keerthana; Parameswaranunni, Reshmibhat; Merzkani, Massini; Molmenti, Ernesto; Bhaskaran, Madhu (International Journal of Angiology, 2020)
Patients with chronic kidney disease (CKD) have an increased likelihood of developing calcific aortic stenosis (AS). These patients also often suffer from multiple comorbidities, potentially making them high-risk surgical candidates and limiting their treatment options. Transcatheter aortic valve replacement (TAVR) is the recommended therapeutic approach for severe AS in patients who are not suitable candidates for surgical aortic valve replacement (SAVR). TAVR is being increasingly considered as a viable alternative to SAVR. As such, its applications in patients with CKD and other chronic diseases, as well as methods to optimize peri- and postoperative results are of great interest and significance. We present the case of a successful renal transplant procedure, performed within a year following a TAVR, in a 52-year-old man who suffered from multiple comorbidities.
Keywords: transcatheter aortic valve replacement; TAVR; renal transplantation; chronic kidney disease; aortic stenosis; ESRD; hemodialysis